Carbon reduction effects of energy transition strategies: a discussion on multi-stakeholder carbon governance - Wang, Shuailong (Frontiers in Environmental Science, 2025)
Investigating the carbon reduction effects of the New Energy cities Demonstration Policy (NECDP) is crucial for promoting the energy transition strategy and meeting the “dual carbon” targets. This study, grounded in stakeholder theory, examines the mechanisms behind the NECDP’s carbon reduction effects from the perspectives of both constraints and incentives. Using panel data from 266 cities at the prefecture level and above in China, A difference-in-differences model and mediation effect model are used to assess the impact and mechanisms of the NECDP on carbon emissions. The study’s results indicate that: 1) The NECDP significantly reduced carbon emissions, and this conclusion holds up after robustness checks that control for other policies and variable replacements. From a dynamic perspective, the carbon reduction effect of the NECDP did not become significant until the third year, suggesting a certain time lag. 2) Mechanism tests show that the NECDP, as a weak constraint and weak incentive environmental policy. It generates both constraints and incentives for environmental stakeholders, such as governments, businesses, and the public. The government enhances environmental oversight and increases investment in technology, while the public becomes more environmentally conscious, engages in green and low-carbon consumption, and participates in environmental regulation. Businesses, in turn, innovate in green technologies and adopt clean, low-carbon production methods, which help drive industrial upgrades and reduce carbon emissions. 3) Heterogeneity analysis shows that the carbon reduction effects of the NECDP are stronger in regions with lower urbanization, fewer resource-based industries, greater digitization, and stronger government environmental focus.